INOVASI PENILAIAN PENGAJARAN BAHASA ARAB UNTUK SISWA DENGAN MODEL PENDEKATAN DIFERENSIASI - Mushlih, Muhammad; Bakar, Yunus Abu (Al-Fakkaar, 2025)
Teaching Arabic in Indonesia faces serious challenges in responding to the diversity of student characteristics, both in terms of ability, background, learning style and motivation. The assessment system which is still dominantly uniform and conventional contributes to inequality in student competency achievement. Based on this reality, this article formulates two main problems: what form of assessment innovation in Arabic language teaching based on a differentiation approach is, and what are the challenges in implementing it in the educational environment. Through a qualitative approach based on literature study, this article explores and analyzes theories and academic findings from the last five years from relevant national literature. The results of the study show that the differentiation approach in assessment offers flexibility and fairness in accommodating student diversity, through various forms of assessment such as projects, portfolios, performance assessments, and student choice-based formative assessments. This innovation allows students to demonstrate their abilities more authentically and meaningfully. However, its implementation still faces a number of challenges, including limited teacher pedagogical literacy, administrative pressure, limited facilities, and an assessment policy system that is not yet fully adaptive to differentiation. It can be concluded that the differentiation approach in assessing Arabic language teaching is a strategic solution in creating learning that is more inclusive and responsive to students’ individual needs.